Assessment of Cognitive Function among Pregnant Women with Anemia in the Early and Late Trimester of Pregnancy - Bibi Sajida, Monica Punshi, Nigar Hashmi, Asia Raza, Komal Zahra, Nargis Gulab, Sadaf Ijaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anemia during pregnancy is a common condition that has been associated with various adverse maternal and fetal outcomes. While its physiological effects are well-documented, its impact on cognitive function remains understudied. Objective: This study aimed to assess and compare cognitive function among pregnant women with anemia in the early and late trimesters of pregnancy. Methods: This observational study was conducted at DHQ hospital KDA Kohat during May 2022 to May 2023. A total of 85 pregnant women were added in the study. They were divided into two groups: 43 women in the early trimester (1st to 2nd month) and 42 women in the late trimester (7th to 9th month) of pregnancy. Results: Cognitive function was significantly lower in the late trimester group compared to the early trimester group, with MMSE scores showing a decline from 23.6 ± 2.8 to 22.3 ± 3.1 (p = 0.03). Attention and working memory, assessed through DST, were also significantly lower in the late trimester (p = 0.02 and p = 0.05). TMT scores indicated slower processing speed in the late trimester (p = 0.003). Fatigue was significantly higher in the late trimester (18.5 ± 4.1 vs. 14.2 ± 3.2, p < 0.001) and was more strongly correlated with cognitive decline than depression. Hemoglobin levels were not significantly different between the groups (p = 0.26), suggesting that factors beyond anemia contribute to cognitive changes in pregnancy. Conclusion: It is concluded that cognitive function declines as pregnancy progresses, with the late trimester group showing greater impairments in attention, memory, and executive function. Keywords: Anemia, Cognitive Function, Pregnancy, Fatigue, Attention, Memory, Executive Function.